Structural Equation Modelling of Factors Influencing Confidence in Mathematics - Bendol, Rechel Legurpa; Dalayap Jr., Reynaldo H. (Bumi Publikasi Nusantara, 2025)
Students’ confidence in mathematics plays a crucial role in determining academic performance, persistence, and interest in STEM pathways. This study aimed to analyze how intrinsic and extrinsic factors influence confidence in mathematics, with self-efficacy as a mediating variable. A descriptive- correlational design was employed, and data were collected through a validated survey from 353 Grade 10 students enrolled in public high schools in Tacurong City during the third quarter of the 2024–2025 school year. Using Structural Equation Modeling (SEM), the study found that both intrinsic and extrinsic factors significantly influence confidence, directly and indirectly, through self-efficacy. Extrinsic factors such as teacher and peer support and intrinsic factors like motivation and prior achievement were positively associated with confidence. Because self-efficacy showed the strongest direct effect, interventions should prioritize building students’ belief in their mathematical abilities. The findings provide evidence for designing policies and practices that support learners’ psychological and contextual needs in mathematics education.